Single‐Dose and Multiple‐Dose Pharmacokinetics of Vaniprevir in Healthy Men. Issue 6 (10th August 2017) - Caro, L; de Hoon, J; Depré, M; Cilissen, C; Miller, J; Gao, W; Panebianco, D; Guo, Z; Troemel, SL; Anderson, MS; Uemura, N; Butterton, J; et al.
Abstract: Vaniprevir is an inhibitor of the hepatitis C virus (HCV) NS3/4A protease. The aim of these double‐blind, placebo‐controlled phase I studies was to evaluate the safety and pharmacokinetics of vaniprevir in healthy male volunteers. The primary objective for both studies was the safety and tolerability of vaniprevir. Single‐dose and steady‐state pharmacokinetics were also assessed. In both studies, there was no apparent relationship between the frequency or intensity of adverse events and vaniprevir dose. At single doses >20 mg, the plasma area under the curve (AUC)0–∞ and maximum concentration (Cmax ) increased in a greater‐than‐dose‐proportional manner. The geometric mean ratios (GMRs; fed/fasted) were 1.22 and 0.79 for AUC0–∞ and Cmax, respectively. Following multiple doses, GMR accumulations for AUC0–12h and Cmax (day 14/day 1) ranged from 1.53 to 1.90 and from 1.41 to 1.92, respectively. These data support the use of vaniprevir with peginterferon and ribavirin in patients with HCV infection.